A Novel Case of Fibroids after Menopause - Jade Edwards; Hamza Katali (Case Reports in Obstetrics and Gynecology)
Fibroids are a condition commonly seen as part of routine gynaecological practice and generally present with menorrhagia, infertility, or pressure symptoms depending on their exact location. We report the case of a postmenopausal 57-year-old lady presenting with left-sided pain and frequency with a complex 15 cm mass mid pelvis and an adjacent additional 7 cm cyst but a risk of malignancy index suggesting benign pathology. She underwent total abdominal hysterectomy (TAH) and right-sided salpingo-oophrectomy (RSO) on recommendation of the multidisciplinary team (MDT) and histology confirmed leiomyomatosis peritonealis disseminata. This rare but important condition is often confused with peritoneal carcinomatosis on imaging. The mainstay of treatment involves lesion and omental excision followed by removal of hormonal stimuli although this approach must be personalised as many younger women may wish to retain their uteri. Long-term follow-up is essential due to the potential for malignant transformation.